ANALISIS ISI FILM “EXHUMA” - Aura Julia Azzahra; Farah Shafira, Virgie Suciana Kusuma, Daffa Eka Putri (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The development of film has grown rapidly from year to year. Various film themes have been presented as a means of entertainment or to convey messages to people. This research aims to describe the message conveyed in a film by analyzing the content qualitatively in the presentation of the story of the film "Exhuma" which is a science fiction horror genre which describes two shamans who work together with a fengshui expert to save A wealthy family experiences a series of supernatural terrors, but it turns out everything is more complicated than just terror